An Analysis of the Effects of Russia’s Invasion to Ukraine on February 24, 2022 on Energy Stocks in Indonesia - Saputro, Arif; Kaluge, David (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The conflict between Russia and Ukraine has had a significant macroeconomic impact, particularly in several economic sectors, including the energy sector, as one of the countries is a major global energy commodity supplier. This study aims to examine the influence of this conflict on Energy stocks, focusing on Abnormal Returns, Trading Volume Activity, Trading Frequency Activity, Bid-Ask Spread, and Market Capitalization. The research employs an Event Study method with a population of 73 companies and a sample of 5 companies based on specific criteria. The results indicate that Abnormal Returns, Bid-Ask Spread returns, and Market Capitalization returns are not significant before and after the event, whereas Trading Volume Activity and Trading Frequency Activity returns are significant both before and after the event